Ammonium and nitrate ratios in the cultivation of tobacco plants - Victor Gabriel Souza de Almeida; Girlene Santos de Souza; Gildeon Santos Brito; Alfredo Teles de Jesus Neto; Cristian Martins de Souza; Anacleto Ranulfo dos Santos (Revista Agrogeoambiental)
Tobacco (Nicotiana tabacum L.) is a plant of the Solanaceae family and native to the Americas. Brazil is one of the largest tobacco producers and exporters worldwide, and this crop guarantees the income of many small rural producers. Tobacco is very demanding of nitrogen, and adequate levels of this nutrient guarantee longevity of the production chain, maximizing productivity and ensuring quality. Therefore, this study aimed to analyze the effect of ammoniacal (NH4+) and nitric (NO3-) nitrogen in the growth and development of tobacco. A randomized design was applied, using five ammonium and nitrate ratios (NH4+:NO3-): 100:0; 75:25; 50:50; 25:75 and 0:100, with five replications. After 60 days of weekly application of the solution, physiological and growth parameters were assessed: chlorophyll contents a and b; number of leaves; plant height; stem diameter; root, stem, leaf, shoot and total dry mass. The 25:75 ratio (NH4+:NO3-) resulted in an increase of height, number of leaves, stem diameter and leaf dry mass, the latter being the variable of greatest commercial relevance for tobacco cultivation. The highest chlorophyll contents were found under the 100:00 ratio (NH4+:NO3-) supplementation; however, this treatment had the lowest expressions in all other variables and is not recommended for tobacco cultivation.